63 Correlation between gait performance and global cognitive functions in senior adults: A systematic review - Joel Acevedo; Joel Acevedo-Nieto; P Karen Martínez; Claudia Amaya; Kun Liu (Journal of Clinical and Translational Science)
Objectives/Goals: Gait performance (GP) and global cognitive functions (GCF) are both critical for maintaining independence and quality of life in senior adults. Recent studies have explored the potential link between GP and GCF, encompassing executive functions. Methods/Study Population: PRISMA guidelines will govern this systematic review. This systematic review synthesizes published research from 2000 to 2024, including peer-reviewed articles, pilot studies, and randomized controlled trials, to examine the relationship between GP (how a person walks and stands) and GCP in older adults. The exclusion criteria will be based on studies focused on physical activities unrelated to balance, meta-analysis, and systematic reviews and those published in languages other than English or Spanish. Results/Anticipated Results: Our preliminary data indicate that gait, or walking speed, is significantly correlated with GCP in older adults, with slower walking associated with poorer global cognition. Specifically, gait speed during dual-task walking shows a strong correlation with working memory (p < .001) and processing speed (p < .05) in individuals aged over 60 years. Gender differences were observed, with women over 80 walking slower than men over 85 years, who walked faster, and women exhibited poorer global cognition than men. Discussion/Significance of Impact: Overall, a gait slowing between 0.68 and 1.1 m per second could predict a marker for the risk of developing dementia, indicating that monitoring gait speed in older adults may provide early warning signs, allowing for timely interventions. Enhancing GP and GCF can improve the quality of life and independence in older adults. Acknowledgments: Research supported by NIH: Award Number HCTRECD R25MD007607 from the NIMHD.